The Phenomenon of Bandung Street Musicians: Interaction with Road Users and Legal Aspects - Rizal, Hendra; Sukmayadi, Yudi (Universitas Negeri Medan, 2023)
The objective of this study is to investigate the phenomenon of street musicians at Bandung Traffic Lights from the perspective of traffic law and road transportation. The research method employed is a qualitative approach with a specific focus on the interaction between road users and aspects of traffic law and road transportation concerning street musicians at Bandung Traffic Lights. The research methodology includes observations, interviews, documentation, and in-depth analysis. The research findings reveal that the presence of street musicians at Bandung Traffic Lights has a diverse impact on commuters; some find it entertaining, while others feel distracted. From the standpoint of traffic and road transport law, the activities of street musicians on the sidewalk or roadway may be considered violations of Article 275, paragraph (1), and Article 28, paragraph (2), of Law No. 22 of 2009 on Traffic and Road Transport. The implications of this study underscore the significance of arts education in fostering a sense of discipline among street musicians. This research can help ensure that their artistic performances are more focused and orderly without causing disruption to road users.